2014
DOI: 10.1590/abd1806-4841.20142679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cases of pemphigus vulgaris and pemphigus foliaceus from a reference service in Pará state, Brazil

Abstract: BACKGROUND Pemphigusis a bullous, rare and chronic autoimmune disease. There are two major forms of pemphigus: vulgaris and foliaceus. Epidemiological data and clinical outcome in patients diagnosed in the Brazilian Amazon states are still rare. OBJECTIVES To study the occurrence of the disease during the study period and analyze the epidemiological profile of patients, the most common subtype of pemphigus, and the clinical evolution of patients. METHODS Retrospective analysis of medical records of hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
2
12
0
9
Order By: Relevance
“…6 and 12 weeks respectively. Similar results were observed in different studies with corticosteroid alone, 17 corticosteroid plus azathioprine 18 and corticosteroid plus rituximab 19 treatment in Pemphigus vulgaris. Corticosteroid decreases inflammation by suppressive effects on cytokines and other mediators of inflammation.…”
Section: Quality Of Lifesupporting
confidence: 77%
“…6 and 12 weeks respectively. Similar results were observed in different studies with corticosteroid alone, 17 corticosteroid plus azathioprine 18 and corticosteroid plus rituximab 19 treatment in Pemphigus vulgaris. Corticosteroid decreases inflammation by suppressive effects on cytokines and other mediators of inflammation.…”
Section: Quality Of Lifesupporting
confidence: 77%
“…La fréquence du pemphigus observée dans notre étude (10 cas/an) était comparable à celle rapportée en Afrique du Sud (9,33 cas/an), mais plus faible qu'en Tunisie (18,4cas/ an) et au Brésil (12,66 cas/an) [12,15,16]. Cette différence pourrait s'expliquer par l'existence de formes endémiques dans ces 2 régions.…”
Section: Discussionunclassified
“…L'âge de survenue semble plus précoce dans le PV (29 ans) que dans les pemphigus superficielles (51 ans). Par contre, le pemphigus survient plus précocément en Tunisie (28 ans) et au Brésil (25 ans), et plus tardivement en Europe (50-70 ans), avec un âge moyen de 62 ans en Allemagne [6,15,16].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…To our knowledge, there is no expressive number of reports concerning PV epidemiology in Brazil. Only one study in NSPS reported an increase in PV cases during a 21-year period, 28 and a smallseries of 20 cases (10 PV cases) in Pará state 33 compared its behavior with PF in the same region. Gonçalves et al 28 demonstrated that new cases of PF were decreasing, being overtaken since 1998 by new cases of PV.…”
Section: Discussionmentioning
confidence: 99%